Susceptibility of Two Varieties of Guava (Psidium guajava L.) to Pest and Disease Infection in the Sub-District of Tanah Sareal, Bogor - Hermanu Triwidodo; Efi Toding Tondok; Desy Nur Avifah (Universitas Gadjah Mada, 2021)
This survey was done in several guava fields around Bogor and found many unhealthy plants infested by various plant pests and diseases. This study aimed to analyze the effect of various guava cultivars on pest and disease intensity on guava in the Sub-District of Tanah Sareal, Bogor. Samples were collected from 20 fields that consisted of 15 samples of Getas Merah and 5 samples of Bangkok Putih cultivars to identify plant pests and diseases. Interviews were done with field owners to obtain information on cultivating practices. Pests found based on morphological identification included plant bugs (Hemiptera: Miridae), locusts (Orthoptera: Acrididae), bagworms (Lepidoptera: Psychidae), Geometrid caterpillars (Lepidoptera: Geometridae), Pyralid caterpillars (Lepidoptera: Pyralidae), scale insects (Hemiptera: Coccidae), planthoppers (Hemiptera: Flatidae), and mealybugs (Hemiptera: Pseudococcidae). Disease and pathogens identified included red rust disease (Cephaleuros sp.), anthracnose (Colletotrichum gloeosporioides), and fruit cancer (Pestalotia sp.). The occurrence of biting-chewing type pests was greater than piercing-sucking type insects, including 33.33% and 34.99%. Red rust disease was the dominant disease found on both guava cultivars consisting of 68.88% and 63.33% of the samples.